Development of Rhodotorula mucilaginosa via Random Mutagenesis for Improved Lipid Production - Wong, Soon Heow (2019)
Oleaginous yeasts are widely used for the production of biodiesel feedstocks because of their high lipid content. In this study, strain improvement was performed on the oleaginous yeast Rhodotorula mucilaginosa to generate mutants with higher lipid yields via random mutagenesis using ethyl methane sulfonate (EMS). Twenty-two mutant isolates prescreened with cerulenin were produced and further characterized via M13 PCR fingerprinting to determine their polymorphism and genetic distances. Eight strains, namely R. mucilaginosa M1, R. mucilaginosa M2, R. mucilaginosa M3, R. mucilaginosa M4, R. mucilaginosa M7, R. mucilaginosa M10, R. mucilaginosa M11 and R. mucilaginosa M18, were chosen based on their genetic distances from the parental strain for biomass production. Six mutants (M1, M2, M3, M4, M7 and M18) showing the highest dry cell weights were further selected for evaluation of lipid production in a laboratory-scale bioreactor using glucose as a carbon source. Results indicated that parental strain exhibited lipid content of 1.83±0.06 g/L, while strains M1, M2, M3, M7 and M18 generated 2.37±0.06 g/L, 2.27±0.06 g/L, 2.27±0.06 g/L, 3.10±0.00 g/L and 3.83±0.15 g/L of intracellular lipid, respectively. These five mutants were identified to have significant increase in lipid production compared to the parental strain. For FAME analysis, two selected strains M7 and M18 comprised of mainly C16 and C18 methyl esters, which are suitable for biodiesel production. This work demonstrated enhanced lipid production in R. mucilaginosa by random mutagenesis. The newly generated strains had higher lipid productivity compared to the parental strain. The application of these strains in industry may reduce the overall cost production of biodiesel.